الحنين إلى الأحبّة في شعر صدر الإسلام - يعقوب, عبد الكريم; حبيب, وهران (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
عرف الشاعر في صدر الإسلام الحب، فتكبد مشقة الفراق وألم الاغتراب عن المحبوبات والزوجات وجسد أنبل العواطف الوجدانية وأصدق المشاعر الإنسانية بعفوية وبساطة، تنمان على عفة التجربة ورهافة الإحساس. وتتقصى هذه الدراسة الأشعار التي أنشدت في الحنين إلى الأحبّة في شعر صدر الإسلام، وتحللها في ظل الحالات النفسية، والظروف التاريخية، والاجتماعية، التي خلقت الإحساس بالغربة، لدى فئة من الشعراء في هذا العصر، وتحاول إبراز المشاعر والأحاسيس التي تولدت من الفقد، والتي عبر عنها الشعراء في أبيات الحنين وقصائده. ففي ظل بعض الظروف الاجتماعية القاسية، يحرم بعض الشعراء نعيم التواصل مع المحبوبات، فيبثون أشواقهم آهاتٍ مفعمة بالشكوى والأنين. ومن الاغتراب في البلاد المفتوحة، والسجون، تتدفق عواطف بعض الشعراء حيال محبوباتهم في الوطن، فينفثونها زفرات مرة نابعة من ألم الفراق والغربة. وتحت وطأة الظروف الصعبة، يتسرع بعض الشعراء في تطليق زوجاتهم، لكن جذوة الحنين المتقدة في الصدور تحرك فيهم حسرات الندم، وتحفزهم على إرجاع زوجاتهم. ووجد بعض الشعراء في المرأة أنموذجاً فنياً يتسع للإيحاء بالمشاعر والأحاسيس، فكانت رمزاً لجملة من المفتقدات افتقدها الشاعر في صدر الإسلام، وعبر عن حاجته إليها في صور رمزية إيحائية تجلت فيها قدرته على توظيف الموروث الشعري لتصوير المواقف، والعواطف، ونقل الأفكار. A poet knew love in the prime of Islam, so he endured the hardship of farewell and the pain of emigration from lovers and wives embodying the noblest affective passions and the most faithful human feelings in a simple, spontaneous way indicating purity of experience and delicacy of sensation. These studies investigate verses which were chanted for the purpose of longing for lovers in the duration of the psychological states and social, historical circumstances that created the feeling of estrangement for a group of poets in this age trying to bring out the feelings and sensations that were brought out of loss which the poets expressed in verses and poems of longing. In the meantime of some social, hard circumstances, some poets are deprived of the pleasure of contact with lovers; therefore, they propagate their yearning as groans full of complaint and moan. And out of emigration in open countries, the poets’ passions towards their lovers at home flow out, so they discharge them as bitter sighs welled out from the pain of farewell and estrangement. Some poets - under the pressure of hard circumstances – hasten to divorce their wives, but the ember of longing which is blazed in chests move sorrows of remorse upon them stimulating them to come back to their wives. Some poets found in the woman an artistic pattern that accommodated inspiration to feelings and sensations. Therefore, she was a symbol for a group of losses the poet had lost in the prime of Islam and expressed his need to her in the form of suggestive, symbolic images in which he revealed his capacity to employ the poetic heritage for portraying situations and passions and for transporting ideas.